The depenalization of marijuana for "therapeutic use" and the social market economy in Tacna, year 2015 - Caballero Laura, Wilfredo Hilario (2018)
The present work deals with "The Decriminalization of Marijuana for therapeutic use and the social market economy in Tacna 2015". The objectives of the present investigation, lead to the legal security of the decriminalization of marijuana for "therapeutic use" and the Social Market Economy. And within it, the specific objectives as they are; the Legislative, Judicial and Political aspects. Applied research, which is aimed at solving the problem. For this purpose, the information obtained through the questionnaire and the interview was used. It has come to conclude that the aspects; Legislative, Judicial, and Political of the Decriminalization of Marijuana for "therapeutic use", positively influence the Social Market Economy.